Rapid and sensitive biomarker detection using molecular imprinting polymer hydrogel and surface-enhanced Raman scattering. Issue 1 (24th January 2018) - Chen, Shaona; Dong, Lijing; Yan, Min; Dai, Zhongxu; Sun, Chenghua; Li, Xin
Abstract : Biomarkers are important biochemical indicators, which could be used for identification, early diagnosis and monitoring of diseases during the course of treatment. However, biomarker diagnosis has some shortcomings such as requiring a large amount of samples, long test time and high cost, which seriously influences the correctness and timely treatment to patients. Here, a relatively fast and efficient plasmonic hot spot-localized surface imprinting of Ag spheres using biomarker template immobilization and hydrogel copolymerization is described. The technique takes a fine control of the imprinting process at the nanometre scale and provides a biosensor with high sensitivity. Proof of the opinion is established by detection of biomarker using surface-enhanced Raman scattering (SERS) spectroscopy. This work represents a valuable step towards SERS with biomarkers for cost-saving and time-saving diagnostic assay. It is expected that the new surface imprinted hydrogel plasmonic material can drive possibilities in advancing application of biomarkers in plasmonic biosensors.